2017
DOI: 10.1097/md.0000000000006941
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-based interaction of the PPARGC1A and UCP1 genes is associated with impaired fasting glucose or type 2 diabetes mellitus

Abstract: The aim of this study is to evaluate the effect of single-nucleotide polymorphisms (SNPs) of the PPARGC1A and UCP1 genes on impaired fasting glucose (IFG) or type 2 diabetes mellitus (T2DM) and the haplotype-based interaction between these genes.A cross-sectional study was conducted by cluster sampling in Henan province, China. Based on the level of fasting plasma glucose (FPG) and the history of T2DM, the participants were divided into 2 groups; 83 individuals were in the IFG+DM group (those with IFG or T2DM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Phasing, also known as haplotype estimation, reconstructs the haplotype sequences from genotype data and has been essential for understanding sequence-specific variation such as allele-specific expression [4, 5], methylation effects [6], and compound heterozygosity [2, 7]. Moreover, numerous studies have shown that haplotype-based association analysis can identify variants that would be missed by a standard single nucleotide polymorphism (SNP)-based analysis [810].…”
Section: Introductionmentioning
confidence: 99%
“…Phasing, also known as haplotype estimation, reconstructs the haplotype sequences from genotype data and has been essential for understanding sequence-specific variation such as allele-specific expression [4, 5], methylation effects [6], and compound heterozygosity [2, 7]. Moreover, numerous studies have shown that haplotype-based association analysis can identify variants that would be missed by a standard single nucleotide polymorphism (SNP)-based analysis [810].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the frequency of AG genotype of A-3826G in persons with CMP ranges from 24% in Italy [ 25 ], to around 50% in Colombia [ 20 ], Japan [ 21 ], and Korea [ 17 ], and to 85% in China [ 19 ]. Similarly, wide frequency ranges have been reported also for the other three SNPs across different populations [ 10 , 20 , 26 , 27 ]. At the same time, some studies report that UCP1 SNPs are strongly associated with disease risk [ 7 , 19 , 28 ], while others report no such findings [ 29 31 ].…”
Section: Introductionmentioning
confidence: 57%
“…For instance, the frequency of AG of A-3826G in persons with CMP ranges from 24% in Italy (22), to around 50% in Colombia (10), Japan (19), and Korea (16), and to 85% in China (18). Similarly wide frequency ranges have been reported also for the other three SNPs across different populations (11,(23)(24)(25). At the same time, some studies report that UCP1 SNPs are strongly associated with disease risk (9,18,26), while others report no such findings (27)(28)(29).…”
Section: Introductionmentioning
confidence: 78%